Determination of thermal expansion coefficient of a monofilament polyamide fiber using digital image correlation. (July 2020) - Mendes, S.S.; Filho, J.C.A.D.; Melo, A.R.A.; Nunes, L.C.S.
Abstract: Coiled polymer actuators are a type of artificial muscles that are a promising development in the field of smart materials. The coefficient of thermal expansion of monofilament polyamide fibers is a crucial parameter for understanding the actuation of coiled fibers. The main purpose of this work is to develop a new methodology for estimating the coefficient of thermal expansion and the transition temperature of monofilament polymer fibers. In the experimental procedure, axial deformations of monofilament polyamide fiber samples were induced by temperature variations using a controlled thermal system. These deformations were determined from images of polyamide samples using the digital image correlation method. Two different approaches based on distinct temperature conditions were conducted. An alternative model with three parameters, including the coefficient of thermal expansion, was introduced to describe the thermal-mechanical behavior of monofilament polyamide fibers. Moreover, polyamide samples were also characterized using four conventional methodologies. Results indicated that the coefficient of thermal expansion changed of a modest negative value to a large negative value and this transition occurred around the glass transition temperature of the polyamide. The thermal expansion curves demonstrate good repeatability and all estimated parameters were in accordance with literature, indicating that the proposed approach can be suitable for the proposed study. This investigation may help in understanding of the intrinsic thermal-mechanical behavior of polymeric monofilaments employed as actuators. Highlights: Performance of twisted than coiled polyamides actuators depends on the thermal response of polyamides fibers. On polymers the coefficient of thermal expansion (CTE) depends on several conditions of the material, including their form. A new methodology for estimating the thermal expansion and Tg of polymer fibers using DIC method is proposed. The CTE changes from a modest negative value to a large negative one and this transition occurred around the Tg. An alternative model was introduced to describe the thermal-mechanical behavior of polyamide samples.